Technical-Tactical Actions Used to Score in Taekwondo: An Analysis of Two Medalists in Two Olympic Championships - Menescardi, Cristina; Falco, Coral; Ros, Concepción; Morales-Sánchez, Verónica; Hernández-Mendo, Antonio (Frontiers in Psychology, 2019)
Research in taekwondo has traditionally focused on specific aspects athletes' overall technical and tactical skills, while ignoring other important issues such as identifying how successful athletes score points. The aim of the current study was to follow two medalists through two Olympic Championships (2012 and 2016) to discover the effective patterns associated with scoring in taekwondo using an observational methodology. An ad-hoc taekwondo observational tool was used to codify the actions performed by the athletes. An observational descriptive and multivariate analysis of 1,688 actions performed by the athletes was conducted. A lag sequential and polar coordinate analysis was performed that considered tactics, techniques and the kicking zone as factors related to score (one to four points). The results showed that one point was scored with direct attacks (DIAs) and actions to the chest where DIAs also occurred prior to scoring. After scoring one-point, opponents tended to gain points by kicking the opponent's head. Two points were scored with simultaneous spinning kicks. Cuts occurred prior to and after scoring while posterior counterattacks (PCAs) occurred after. Three points were scored by performing indirect attacks and PCAs to the head. Cuts, dodges, and linear actions preceded the three-point score while dodges, DIAs, and linear actions to the chest also occurred after the three point-actions. In conclusion, these two athletes not only mastered the whole tactics but also used specific strategies to score. That is, they anticipated the opponent's attack to score one point by kicking the opponent directly and performed spinning kicks from short distances when they perceived an opponent's cutting action to score two points. Finally, these athletes indirectly attacked the opponent when they dodged by kicking their head and counterattacked posteriorly when an opponent's cut was perceived to score three points. Thus, they used the most difficult tactics to achieve the highest score. It is suggested that coaches and psychologists train athletes in better decision-making by preparing them to not only prepare their own attacks but to systematically use the intended attacks by their opponents to score their own points in accordance with the successful patterns extracted in this study.